Trend and Multi‐Frequency Analysis Through Empirical Mode Decomposition: An Application to a 20‐Year Record of Atmospheric Carbonyl Sulfide Measurements. Issue 3 (27th January 2023) - Serio, C.; Montzka, S. A.; Masiello, G.; Carbone, V.
Abstract: The Empirical Mode Decomposition (EMD) is a fully non‐parametric analysis of frequency modes and trends in a given series that is based on the data alone. We have devised an improved strategy based on a series of best practices to use EMD successfully in the analysis of the monthly time series of carbonyl sulfide (OCS) atmospheric mole fractions measured at NOAA network stations (2000–2020). Long‐term trends and intra‐ and inter‐annual variability has been assessed. After a phase of generally increasing mole fractions up to 2015, with a temporary decline around 2009, we found that the OCS atmospheric mole fraction subsequently decreased at all stations, reflecting a recent imbalance in its total sources and losses. Our analysis has revealed a characteristic time scale for variation of 8–10 years. The variance associated with this long‐term behavior ranges from ∼ $\sim $ 15% to 40% of the total strength of the signal, depending on location. Apart from this complex long‐term behavior, the OCS time series show a strong annual cycle, which primarily results from the well‐known OCS uptake by vegetation. In addition, we have also found one more frequency of minor variance intensity in the measured mole fraction time‐history, which corresponds to periods in the range of 2–3 years. This inter‐annual variability of OCS may be linked to the Quasi‐Biennial Oscillation. Plain Language Summary: The Empirical Mode Decomposition has arisen as a new paradigm for the processing and analysis of time series. The tool has been applied to multi‐year mole fraction measurements of an atmospheric gas, carbonyl sulfide (OCS), which has important implications for understanding and analyzing the carbon cycle. OCS is the most abundant sulfur‐containing trace gas in the atmosphere and has recently emerged as a putative proxy for the terrestrial photosynthetic uptake of CO2 because OCS and CO2 have the same diffusion pathway into leaves. The study has analyzed OCS at 14 cooperative stations, which are distributed all around the world. We have found a characteristic time scale for 8–10 years variation. Apart from this complex long‐term behavior, the OCS time series show a robust yearly cycle, primarily from OCS uptake by vegetation. Finally, we have also found one more frequency, which corresponds to periods in the range of 2–3 years. This inter‐annual variability of OCS may be linked to the Quasi‐Biennial Oscillation, which is an almost periodic oscillation of the winds of the equatorial stratosphere. Key Points: Atmospheric carbonyl sulfide has decreased at NOAA network stations in recent years Time Series Analysis and trend identification Empirical Mode Decomposition identified many characteristic frequencies of variability, some compatible with Quasi Biennal Oscillation